Journeys from quantum optics to quantum technology. (August 2017) - Barnett, Stephen M.; Beige, Almut; Ekert, Artur; Garraway, Barry M.; Keitel, Christoph H.; Kendon, Viv; Lein, Manfred; Milburn, Gerard J.; Moya-Cessa, Héctor M.; Murao, Mio; Pachos, Jiannis K.; Palma, G. Massimo; et al.
Abstract: Sir Peter Knight is a pioneer in quantum optics which has now grown to an important branch of modern physics to study the foundations and applications of quantum physics. He is leading an effort to develop new technologies from quantum mechanics. In this collection of essays, we recall the time we were working with him as a postdoc or a PhD student and look at how the time with him has influenced our research.